Berlin Exile - Krauss, Susanne (Germany, 2010)
In early 2008, news reports about the unrest in Tibet flicker across TV screens in German living rooms - but they cannot truly report, due to censorship and gag orders from the Chinese government. Tibetan exiles all over the world hold synchronized demonstrations for basic human rights, such as freedom of speech and of the press. The few Berliner Tibetans join in as well, taking vehemently to the streets for months on end; they seem to feel a sense of duty to exercise this new-found right to demonstration. 'Berlin Exile' is a film about life in exile, and a snapshot of a confused fight for a moment of attention in the eyes and ears of the worldwide media.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films